Application of dual tree complex wavelet transform in tandem mass spectrometry. (1st August 2015) - Murugesan, Selvaraaju; Tay, David B.H.; Cooke, Ira; Faou, Pierre
Abstract: Mass Spectrometry (MS) is a widely used technique in molecular biology for high throughput identification and sequencing of peptides (and proteins). Tandem mass spectrometry (MS/MS) is a specialised mass spectrometry technique whereby the sequence of peptides can be determined. Preprocessing of the MS/MS data is indispensable before performing any statistical analysis on the data. In this work, preprocessing of MS/MS data is proposed based on the Dual Tree Complex Wavelet Transform (DTCWT) using almost symmetric Hilbert pair of wavelets. After the preprocessing step, the identification of peptides is done using the database search approach. The performance of the proposed preprocessing technique is evaluated by comparing its performance against Discrete Wavelet Transform (DWT) and Stationary Wavelet Transform (SWT). The preprocessing performed using DTCWT identified more peptides compared to DWT and SWT. Abstract : Highlights: Application of dual tree complex wavelet transform in tandem mass spectroscopy. New class of almost symmetric wavelet used to denoise MS/MS data. Results in a better detection of peptides in biological samples.